2023
DOI: 10.1002/nop2.2048
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' knowledge and attitudes towards surgical site infection and surveillance: A quasi‐experimental study

Sinéad Horgan,
Jonathan Drennan,
Emmet Andrews
et al.

Abstract: AimSSI is one of the most prevalent healthcare‐associated infections and is associated with extended hospital stays, increased need for reoperation and higher hospital readmission rates. Implementing systematic SSI surveillance can reduce these adverse outcomes. Implementing a surveillance system into a hospital is a complex intervention requiring that staff involved in a patient's perioperative journey have the knowledge of SSI prevention, the data required for surveillance, an understanding of how data infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…[20] Studies in Ethiopia and Cameroon reveal insufficient knowledge and practice among nurses in preventing SSIs due to factors like limited experience, education, workload, infection prevention training, and patient safety guidelines. [21,22] In addition, another study conducted in Ethiopian showed that the level of practice of nurses towards the prevention of SSIs was poor. [23] The literature on factors contributing to inadequate knowledge and practice in Rwanda regarding SSIs prevention among healthcare professionals is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Studies in Ethiopia and Cameroon reveal insufficient knowledge and practice among nurses in preventing SSIs due to factors like limited experience, education, workload, infection prevention training, and patient safety guidelines. [21,22] In addition, another study conducted in Ethiopian showed that the level of practice of nurses towards the prevention of SSIs was poor. [23] The literature on factors contributing to inadequate knowledge and practice in Rwanda regarding SSIs prevention among healthcare professionals is limited.…”
Section: Introductionmentioning
confidence: 99%